TECHNICAL EFFICIENCY OF ISLAMIC BANKS IN SELECTED AFRICAN COUNTRIES - Jimoh, Abdulrazaq T.; Attah, John A.; Abdulmumin, Biliqees A.; Abdul, Falilat A. (International Journal of Sukuk and Waqf Research, 2021)
The size of banking market for Islamic banks in Africa is relatively small. This poses serious threat to the level of competition with conventional ones unless they are technically efficient. Unfortunately, available evidences have shown that Islamic banks in Africa are technically inefficient, though no consensus have been reached on the source(s) of such inefficiency. Therefore this study investigated the technical efficiency of Islamic banks in Africa with particular emphasis pure technical and scale efficiencies. Convenient sampling technique was used to select a sample of 36 Islamic banks for eight (8) years from 2012 to 2019. Data were collected for input and output variables from annual reports of the banks. Data Envelopment Analysis (DEA) was used to analyse the data by estimating the efficiency scores for the banks. The efficiency scores of 0.764 (ar<1), 0.850 (ar<1) and 0.896 (ar<1) for OTE, PTE and SE respectively indicate that on average, the selected banks were technically inefficient. The study concluded that Islamic banks in Africa were technically inefficient due mainly to pure technical inefficiencies such as poor managerial performance. The study then recommended employment and training of staff with requisite skills and knowledge of Islamic banking and finance, to enhance managerial performance and boost their technical efficiency of the banks. JEL Classification Codes: G21.